2019
DOI: 10.3390/nu11020218
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Effects of Mangiferin and Z-Ligustilide in PAH-Exposed Human Airway Epithelium in Vitro

Abstract: According to World Health Organisation (WHO) air pollution increases the risk of cardiovascular disorders, respiratory diseases, including COPD, lung cancer and acute respiratory infections, neuro-degenerative and other diseases. It is also known that various phytochemicals may mitigate such risks. This study tested if phytochemicals mangiferin (MNG) and Z-ligustilide (Z-LG) may protect PAH-exposed human lung bronchial epithelial cells (BEAS-2B). Organic PAH extract was obtained from the urban fine PM with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
(70 reference statements)
1
9
0
Order By: Relevance
“…A similar observation was recorded after exposure of HepG2 cells to B[a]P [8]. Furthermore, Grauzdytė et al [18] reported a significant reduction in cell proliferation accompanied by production of oxidative stress in the human bronchial epithelial cells BEAS-2B exposed to PAH extracts. During the metabolism of PAHs, ROS such as superoxide anions, H 2 O 2 , and hydroxyl radicals could be generated [19].…”
Section: Resultssupporting
confidence: 69%
“…A similar observation was recorded after exposure of HepG2 cells to B[a]P [8]. Furthermore, Grauzdytė et al [18] reported a significant reduction in cell proliferation accompanied by production of oxidative stress in the human bronchial epithelial cells BEAS-2B exposed to PAH extracts. During the metabolism of PAHs, ROS such as superoxide anions, H 2 O 2 , and hydroxyl radicals could be generated [19].…”
Section: Resultssupporting
confidence: 69%
“…Mangiferin ameliorated oxidative stress in vitro through inhibiting ROS level [ 38 ]. High-dose silymarin (50 mg/kg/day) administration prevented CS-induced elevation in MDA levels and decrease in SOD activities in vivo [ 30 ].…”
Section: Roles Of Flavonoids On Chronic Obstructive Pulmonary Disementioning
confidence: 99%
“…The NPs were developed following the method of solvent evaporation [52] using 15 mg of PLGA (75:25) and adding 500 µL of DCM in a flask. The aqueous phase composition was 5 mL of PVA solution (0.5%), and the quantity of mangiferin was added according to the amount required (Figure 1).…”
Section: Preparation Of Nanoparticles (Nps)mentioning
confidence: 99%